Natural history collections are critical resources for contemporary and future studies of urban evolution. (2nd July 2020) - Shultz, Allison J.; Adams, Benjamin J.; Bell, Kayce C.; Ludt, William B.; Pauly, Gregory B.; Vendetti, Jann E.
Abstract: Urban environments are among the fastest changing habitats on the planet, and this change has evolutionary implications for the organisms inhabiting them. Herein, we demonstrate that natural history collections are critical resources for urban evolution studies. The specimens housed in these collections provide great potential for diverse types of urban evolution research, and strategic deposition of specimens and other materials from contemporary studies will determine the resources and research questions available to future urban evolutionary biologists. As natural history collections are windows into the past, they provide a crucial historical timescale for urban evolution research. While the importance of museum collections for research is generally appreciated, their utility in the study of urban evolution has not been explicitly evaluated. Here, we: (a) demonstrate that museum collections can greatly enhance urban evolution studies, (b) review patterns of specimen use and deposition in the urban evolution literature, (c) analyze how urban versus rural and native versus nonnative vertebrate species are being deposited in museum collections, and (d) make recommendations to researchers, museum professionals, scientific journal editors, funding agencies, permitting agencies, and professional societies to improve archiving policies. Our analyses of recent urban evolution studies reveal that museum specimens can be used for diverse research questions, but they are used infrequently. Further, although nearly all studies we analyzed generated resources that could be deposited in natural history collections (e.g., collected specimens), a minority (12%) of studies actually did so. Depositing such resources in collections is crucial to allow the scientific community to verify, replicate, and/or re‐visit prior research. Therefore, to ensure that adequate museum resources are available for future urban evolutionary biology research, the research community—from practicing biologists to funding agencies and professional societies—must make adjustments that prioritize the collection and deposition of urban specimens.